2017
DOI: 10.3390/ijerph14040343
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Injuries and Violence among Adults in Northern Jordan: A Hospital-Based Retrospective Study

Abstract: Injuries (unintentional and intentional) are the main cause of death and disability worldwide, including Jordan. The main purpose of this hospital-based retrospective study was to identify characteristics, causes, and risk factors of unintentional injuries and violence among all adult patients who approached the Accidents and Emergency department because of injury in Northern Jordan. Data were collected retrospectively from four major hospitals from January 2008 to January 2013. A total of 2425 Jordanian indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
7
9
0
Order By: Relevance
“…The mean age of victims in the UAE and our study was 30 and 31 years respectively. Male predominance among the victims was evident in our study (90%) , UAE (85%) and Jordan (87%) studies [17,21]. Our study demonstrated that females were more likely to sustain SII when compared to the IPV group in which males were prevalent.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The mean age of victims in the UAE and our study was 30 and 31 years respectively. Male predominance among the victims was evident in our study (90%) , UAE (85%) and Jordan (87%) studies [17,21]. Our study demonstrated that females were more likely to sustain SII when compared to the IPV group in which males were prevalent.…”
Section: Discussionsupporting
confidence: 49%
“…Such studies are very rare in the Arabian Gulf region. A hospitalbased retrospective study in Jordan demonstrated that violence (71%) was the most frequent cause of ED visits followed by road tra c injuries (23%) [17].…”
Section: Discussionmentioning
confidence: 99%
“…A prior study conducted in Jordan in accidents and emergency departments revealed that the violence was the most common reason of injury (71%) and males (87%) were the main victims [11]. Although there is a paucity of information on violence-related injuries in the Arabian Gulf region, there are some studies which addressed the violence-related trauma by focusing either on mechanism of injury, age group or gender.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age in the UAE and our study was 30 and 31 years respectively. Similarly, male predominance among the victims was also evident in the UAE (85%) and Jordan (87%) based studies [17,21].…”
Section: Discussionmentioning
confidence: 68%
“…Such studies based on trauma registry data are very rare in the Arabian Gulf region. A hospital-based retrospective study in Jordan demonstrated that violence (71%) was the most frequent cause of ED visits followed by road tra c injuries (23%) [17] Bala et al studied the prevalence of physical ghting and its associated factors among adolescent population in Qatar [18]. This study was based on a student health survey in school to determine the prevalence and factors associated with being engaged in a physical ght.…”
Section: Discussionmentioning
confidence: 99%